Response of ecological indices to nutrient and chemical contaminant stress factors in Eastern Mediterranean coastal waters. (November 2016) - Simboura, N.; Pavlidou, A.; Bald, J.; Tsapakis, M.; Pagou, K.; Zeri, Ch.; Androni, A.; Panayotidis, P.
Highlights: ⿢ Primary production indices most sensitive to particulates and nitrogen. ⿢ Secondary production indicators (benthos) most sensitive to phosphorus. ⿢ A physicochemical status indicator firstly applied in Eastern Mediterranean. ⿢ Decision tree successfully assessed major stress factors⿿ impact. ⿢ Macroalgae reflected the impact of multiple pressures on the coasts. Abstract: Environmental data produced throughout monitoring activities in the framework of the implementation of Water Framework Directive 2000/60/EC (WFD) in Eastern Mediterranean (Greece) were used to assess the sensitivity and response of ecological indices against trace metals, eutrophication and multiple stress factors. The applied ecological indices include multi-metric eutrophication indices, a physicochemical status index applied for the first time in the Greek marine area, benthic indices, phytoplankton biomass index, and integrated status indices assessed through the application of the decision tree integration scheme. To investigate the exceedances in the eco-stoichiometric relationship between nutrients, considered a stressing factor, all physicochemical elements influenced directly or indirectly by eutrophication, such as nutrient concentrations, water transparency, oxygen saturation, particulates concentration, and sediment organic content, were related to ecological indices. Also, chemical contaminant stress factors represented by heavy metal concentrations in the water, as well as multiple stress factors represented by a pressure index, were related to ecological indices. A graphical visualization multivariate tool and statistical correlations were used to evaluate the sensitivity or explanatory power of the tested ecological indices against single and multiple stress factors. Results showed a strong response of all ecological indices to stress factors, although a diversification of sensitivity was evident. Primary production-related indices, i.e., macroalgae and chlorophyll- a indices, are more sensitive to particulates and nitrogen, while secondary production-related indices, i.e., benthic macroinvertebrates indices and eutrophication indices, including nutrients, are more sensitive to phosphates in the water column. The macroalgae index shows the strongest sensitivity to multiple stress factors. Among metals, mostly cadmium seems to match all indices⿿ performance. Nutrient relationships were shown as critical to eutrophication and ecological status.